Implementasi Sistem Informasi Pengelolaan Sampah di Dinas Lingkungan Hidup Kota Tegal - Dicky Lintang Prasetyo (Journal of Engineering and Applied Technology, 2025)
This study aims to evaluate and implement a waste management information system at the Tegal City Environment Agency to improve the effectiveness and efficiency of waste data management. The study was conducted through two months of fieldwork, focusing on the development of a web-based system using PHP, MySQL, and Visual Studio Code. This system includes user registration, login authentication, waste bank transaction data processing, and an administrative dashboard display. The implementation results show that this information system is capable of speeding up the recording process, reducing input errors, and increasing the transparency and accuracy of waste management data. In addition, this system also facilitates interaction between the community and the managing agency through easy access and real-time data presentation. The significance of this research lies in its contribution to supporting cleaner, more efficient, and sustainable environmental management, while also serving as the basis for the development of more modern waste management information systems in the future.